Examining conspiracy beliefs and COVID-19 in four countries: The role of disgust towards the political system and implications for prosocial behavior. (November 2021) - Moon, Chanki; Travaglino, Giovanni A.
Since late 2019, the coronavirus SARS-COV-2 responsible for the COVID-19 disease has continued to spread across different regions of the world. As a result, governments have been implementing measures for controlling the disease which rely on people's cooperation. In this research, we considered predictors and implications of people's beliefs that they "haven't been told the 'whole story' about COVID-19." Specifically, we examined the role of disgust towards the political system in predicting conspiratorial tendencies across four countries, in Europe (Italy and the UK), North America (the USA), and Asia (South Korea). In addition, we investigated the implications of conspiratorial beliefs for individuals' intentions to engage in prosocial cooperative behavior. In line with the idea that feelings of disgust towards the political system may indicate that people perceive the system as violating core norms, results showed that disgust was associated with stronger conspiratorial tendencies. Individuals' conspiratorial tendencies were in turn associated with lower intentions to help others during the pandemic. Results were broadly consistent across the countries tested. Directions for future research are discussed.